Tourism versus the transformation of ksours – Southern Morocco case study - Dłużewska Anna; Dłużewski Maciej (Bulletin of Geography. Socio-Economic Series)
Ksours form a cultural landscape for most of the countries of North Africa. They are an important part of the cultural heritage of the desert areas in Algeria, Libya, Tunisia, Mali or Morocco. They also become an undeniable attraction for tourism. The article looks at the impact of tourism on the transformation of ksours. It is based on comparative field research in the Dadès-Drâa Valley (Southern Morocco), the region of the highest ksour concentration. The results show that despite being very close to most sustainable tourism indicators, the whole impact of tourism is rather negative. Tourism is creating social disproportions, being the first incentive to abandon the ksours by those who are not involved in the sector. This is leading to the destruction of particular houses first, and later to the destruction of the whole village. The revitalization of ksours remains a theoretical solution only; thus the author suggests paying greater attention to social equity in order to stop the transformation of ksours at the 2nd stage of development.